TÌM X
\(8^x.16^{-2x}=4^5\)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
2: \(3x\left(x-4\right)+2x-8=0\)
=>\(3x\left(x-4\right)+2\left(x-4\right)=0\)
=>\(\left(x-4\right)\left(3x+2\right)=0\)
=>\(\left[{}\begin{matrix}x-4=0\\3x+2=0\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=4\\x=-\dfrac{2}{3}\end{matrix}\right.\)
3: 4x(x-3)+x2-9=0
=>\(4x\left(x-3\right)+\left(x+3\right)\left(x-3\right)=0\)
=>\(\left(x-3\right)\left(4x+x+3\right)=0\)
=>\(\left(x-3\right)\left(5x+3\right)=0\)
=>\(\left[{}\begin{matrix}x-3=0\\5x+3=0\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=3\\x=-\dfrac{3}{5}\end{matrix}\right.\)
4: \(x\left(x-1\right)-x^2+3x=0\)
=>\(x^2-x-x^2+3x=0\)
=>2x=0
=>x=0
5: \(x\left(2x-1\right)-2x^2+5x=16\)
=>\(2x^2-x-2x^2+5x=16\)
=>4x=16
=>x=4
a) ( x + 2 )( x + 3 ) - ( x - 2 )( x + 5 ) = 16
<=> x2 + 5x + 6 - ( x2 + 3x - 10 ) = 16
<=> x2 + 5x + 6 - x2 - 3x + 10 = 16
<=> 2x + 16 = 16
<=> 2x = 0
<=> x = 0
b) 3x( 2x - 4 ) - 2x( 3x + 5 ) = 44
<=> 6x2 - 12x - 6x2 - 10x = 44
<=> -22x = 44
<=> x = -2
c) 2( 5x - 8 - 3 )( 4x - 5 ) = 4( 3x - 4 )
<=> 2( 5x - 11 )( 4x - 5 ) = 4( 3x - 4 )
<=> 2( 20x2 - 69x + 55 ) = 12x - 16
<=> 40x2 - 138x + 110 = 12x - 16
<=> 40x2 - 138x + 110 - 12x + 16 = 0
<=> 40x2 - 150 + 126 = 0 ( chưa học nghiệm vô tỉ nên để vô nghiệm nha :) )
=> Vô nghiệm
a) \(\Rightarrow72-20x-36x+84=30x-240-6x-84\)
\(\Rightarrow80x=480\Rightarrow x=6\)
b) \(\Rightarrow15x+25-8x+12=5x+6x+36+1\)
\(\Rightarrow4x=0\Rightarrow x=0\)
c) \(\Rightarrow10x-16-12x+15=12x-16+11\)
\(\Rightarrow14x=4\Rightarrow x=\dfrac{2}{7}\)
1: =>x^2+4x-21=0
=>(x+7)(x-3)=0
=>x=3 hoặc x=-7
2: =>(2x-5-4)(2x-5+4)=0
=>(2x-9)(2x-1)=0
=>x=9/2 hoặc x=1/2
3: =>x^3-9x^2+27x-27-x^3+27+9(x^2+2x+1)=15
=>-9x^2+27x+9x^2+18x+9=15
=>18x=15-9-27=-21
=>x=-7/6
6: =>4x^2+4x+1-4x^2-16x-16=9
=>-12x-15=9
=>-12x=24
=>x=-2
7: =>x^2+6x+9-x^2-4x+32=1
=>2x+41=1
=>2x=-40
=>x=-20
\(8^x.16^{-2x}=4^5=>\frac{8^x.1}{16^{2x}}=4^5=>\frac{8^x}{256^x}=4^5=>\frac{1}{32^x}=4^5=>4^5.32^x=1=>2^{10}.2^{5x}=1\)
\(2^{10+5x}=1=>10+5x=0=>5x=-10=>x=-2\)
\(8^x.16^{-2x}=4^5\)
\(\Leftrightarrow8^x.8^{-2x}.2^{-2x}=4^5\)
\(\Leftrightarrow8^{x+\left(-2x\right)}.2^{-2x}=\left(2^2\right)^5\)
\(\Leftrightarrow8^{-x}=2^{10}:2^{-2x}\)
\(\Leftrightarrow8^{-x}=2^{10-\left(-2x\right)}=2^{10+2x}\)
\(\Leftrightarrow\left(2^3\right)^{-x}=2^{10+2x}\)
\(\Leftrightarrow2^{-3x}=2^{10+2x}\)
\(\Leftrightarrow-3x=10+2x\)
\(\Leftrightarrow5x=-10\)
\(\Leftrightarrow x=-2\)
Vậy : \(x=-2\)